Preparation method of bone nail based on photocuring silk fibroin
Through the preparation method of bone nails based on photocured silk fibroin, the problem that fracture internal fixation materials in the prior art are difficult to meet the mechanical strength, in vivo degradability and degradation products are harmless to the human body, and the high mechanical of bone nails is achieved Performance and good biocompatibility.
Patent Information
- Application Number
- CN202411423540.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing internal fixation materials for fractures are difficult to meet the requirements of mechanical strength, in vivo degradability and degradation products that are harmless to the human body, especially in the treatment of large-scale fractures.
The preparation method of bone nails based on photocured silk fibroin is adopted. After mixing the post-silicon fibroin solution, riboflavin aqueous solution and hydrogen peroxide solution, photocuring is carried out under ultraviolet light to form silk fibroin bone nails, and the Dehydration of anhydrous ethanol enhances mechanical properties.
It achieves good mechanical properties of bone nails, and the compressive strength reaches about Young's modulus of about 160 MPa. It also has good biocompatibility and human degradability, and the degradation products are harmless to the human body.
Smart Images

Figure CN119499458A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a manufacturing process of a bone nail, belongs to the field of polymer gel, and in particular to a preparation method of a bone nail based on light-cured silk fibroin. Background Art
[0002] Fractures are a common disease that people face in life and have always troubled people. The long healing time and the easy occurrence of osteoporosis symptoms during the healing process are the main reasons why people suffer from pain during the fracture repair process.
[0003] At present, many materials are used for bone fixation in fracture treatment, such as traditional metal materials such as titanium alloy and stainless steel. However, metals are non-degradable and require a second surgery to remove, which increases the pain of treatment. At the same time, metals are corrosive and can cause inflammatory reactions. Patients need to endure great pain throughout the process. For this reason, polymer materials that can be degraded by the human body have been introduced into the field of bone fixation.
[0004] At present, polylactic acid, a polymer material that can be degraded by the human body, is recognized clinically for its excellent mechanical properties, and its degradation product, lactic acid, can directly participate in human metabolism. However, the large amount of lactic acid produced by the degradation of polylactic acid is corrosive to host tissues, causing discomfort to the human body and even leading to bone dissolution, and cannot be used for large-area fracture treatment. In view of the problems existing in clinical fracture internal fixation materials, how to ensure the mechanical strength and in vivo degradability of internal fixation materials while ensuring that the degradation products are harmless to the human body and have good biocompatibility is still a hot topic of concern for scientists.
[0005] The Chinese invention patent application with application number 202111176683.2 and application date 2021.10.09 discloses a biological bone nail material and a preparation method thereof, which is a material with an open-cell structure made by physical injection molding and foaming using a blend of polylactic acid and polycaprolactone as the base; during preparation, a twin-screw extruder is first used to melt plasticize and extrude granules to obtain a base product, and then the base product is physically injection molded and foamed in a special foaming injection molding machine barrel to obtain a biological bone nail material. Although the material is biodegradable and has a certain lightweight effect, it still has the following disadvantages: The material uses polylactic acid as its main component, with a content of up to 75%-95%. Therefore, after degradation, it will produce a large amount of lactic acid, which will corrode human tissue and damage the biocompatibility effect.
[0006] The information disclosed in this background technology section is only intended to increase the understanding of the overall background of the application, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art already known to ordinary technicians in this field. Summary of the invention
[0007] The purpose of the present invention is to overcome the defects and problems existing in the prior art that cannot simultaneously meet the requirements of mechanical strength, in vivo degradability, and harmlessness of degradation products to the human body, and to provide a method for preparing bone nails based on photocured silk fibroin that can simultaneously meet the requirements of mechanical strength, in vivo degradability, and harmlessness of degradation products to the human body.
[0008] To achieve the above objectives, the technical solution of the present invention is: a method for preparing a bone nail based on light-cured silk fibroin, the preparation method comprising the following steps: The first step: firstly, the silk fibroin solution and the riboflavin aqueous solution are uniformly mixed to obtain a mixed solution, and then the hydrogen peroxide solution is added to the mixed solution to mix to obtain a precursor solution; The concentration of the silk fibroin solution is 8-15wt%, the concentration of the riboflavin aqueous solution is 0.05-10mmol / L, and the volume ratio between the silk fibroin solution and the riboflavin aqueous solution is 5-20:1; Step 2: first pour the precursor solution into a light-transmitting bone screw mold, and then place the bone screw mold under ultraviolet light for illumination to cause a photocuring reaction until the precursor solution is completely gelled; Step 3: First, place the bone screw mold in a freezing environment for demoulding, then place the removed bone screw blank in anhydrous ethanol for dehydration, and then dry it to obtain the bone screw.
[0009] In the second step, the parameters of the ultraviolet light irradiation are: the power of the ultraviolet lamp is 100-900W, and the light curing reaction time is 2-30min.
[0010] In the first step, the process for obtaining the post-silk fibroin solution is as follows: first obtain a pre-silk fibroin solution with a concentration of 1.5-7wt%, then put the pre-silk fibroin solution into a dialysis bag, and then place the dialysis bag into a polyethylene glycol solution with a mass percentage concentration of 10%-30% for concentration, until the concentration of the pre-silk fibroin solution is concentrated to 8-15wt%, thereby obtaining the post-silk fibroin solution.
[0011] The concentration time is 8-12 hours.
[0012] The process for obtaining the pre-silk fibroin solution is as follows: firstly, raw silk is placed in a sodium carbonate aqueous solution for heating and soaking to perform degumming treatment to obtain degummed silk fibroin fibers, then the degummed silk fibroin fibers are immersed in a LiBr aqueous solution for heating and dissolution to obtain a crude solution, then the crude solution is placed in a dialysis bag, and then the dialysis bag is placed in deionized water for low-temperature dialysis, the temperature of the low-temperature dialysis is 0-4°C, the time of the low-temperature dialysis is 1-5 days, then the remaining solution in the dialysis bag after dialysis is filtered to obtain a filtrate, and then the filtrate is diluted with deionized water to obtain a pre-silk fibroin solution, and the concentration of the pre-silk fibroin solution is 1.5-7wt%.
[0013] The concentration of the sodium carbonate aqueous solution is 0.1-0.5wt%, the mass volume ratio between the raw silk and the sodium carbonate aqueous solution is 1g / 10-100mL, the temperature of the degumming treatment is 45-100°C, and the time of the degumming treatment is 1-8h.
[0014] The concentration of the LiBr aqueous solution is 1-10 mol / L, the mass volume ratio between the degummed silk fiber and the LiBr aqueous solution is 1 g / 1-20 mL, the heating and dissolving temperature is 45-85° C., and the heating and dissolving time is 0.5-3 h.
[0015] In the first step, the volume percentage concentration of the hydrogen peroxide solution is 5%-30%, and the volume ratio between the hydrogen peroxide solution and the mixed solution is 1:5-30.
[0016] In the third step, the dehydration time of the anhydrous ethanol is 12-72 hours.
[0017] In the third step, the drying temperature is 40-80°C.
[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. In the preparation method of a bone nail based on light-cured silk fibroin of the present invention, a high-concentration raw silk fibroin solution is used as the basis, and a riboflavin solution and a hydrogen peroxide solution are used as the light-curing system. The silk fibroin bone nail is first cured under ultraviolet light, and then dehydrated by anhydrous ethanol to enhance the mechanical properties of the bone nail, which creates favorable conditions for one-step molding of the bone nail. The advantages of this design include: First point: The size of the bone screw is 2mm-5mm, which can meet the needs of bone screws for fractures; Second point: The high concentration of silk fibroin solution and dehydration with anhydrous ethanol ensured the good mechanical properties of the bone screw. The compressive strength of the dry bone screw reached a Young's modulus of about 160 MPa. The mechanical strength greatly exceeded the strength requirement of human cancellous bone, providing a theoretical basis for the dry bone screw to be implanted into human cancellous bone. Third point: The main raw materials are raw silk fibroin, riboflavin, and hydrogen peroxide, and no organic reagents are added during the preparation process. Among them, silk fibroin and riboflavin have good biocompatibility, and the amount of hydrogen peroxide is negligible. It will also be consumed during the gelation process under ultraviolet light irradiation and will not cause cytotoxicity. It has strong human degradability and will not produce degradation products that are harmful to human health. Therefore, the present invention can simultaneously meet the advantages of mechanical strength, in vivo degradability, and the degradation products being harmless to the human body, and has good market application prospects in the field of bone repair.
[0019] 2. In the preparation method of a bone nail based on light-cured silk fibroin of the present invention, the precursor solution used is a mixture of a silk fibroin solution, a riboflavin aqueous solution, and a hydrogen peroxide solution, wherein the silk fibroin is based, and riboflavin and hydrogen peroxide are used as a light-curing system, and the silk fibroin hydrogel is cured under ultraviolet light. During the reaction, hydrogen peroxide decomposes under ultraviolet light to produce oxygen, and riboflavin is first excited to produce a triplet state under ultraviolet light, and then reacts with the oxygen produced by hydrogen peroxide to form oxygen free radicals, and then the oxygen free radicals promote the interaction between the silk fibroin macromolecules. The entanglement forms a gel (i.e., riboflavin and H2O2 undergo a continuous photo-crosslinking cycle reaction, promoting the conversion of tyrosine to dityrosine, and playing a role in catalyzing gelation). It can be seen that hydrogen peroxide, as an oxygen source, can provide more oxygen for the photocuring system, continuously promoting the continuous progress of the reaction, greatly shortening the time for gel formation, and improving the production efficiency of bone screw blanks. At the same time, the use of bone screw molds (preferably made of PDMS material) can form bone screws in one step, greatly shortening the preparation time, thereby shortening the production time of bone screws as a whole, and is particularly suitable for mass production of bone screws. Therefore, the production time of the present invention is short, and it is suitable for mass and large-scale production.
[0020] 3. In the method for preparing a bone nail based on light-cured silk fibroin of the present invention, a hydrogen peroxide solution is introduced to improve production efficiency. At the same time, the use of the hydrogen peroxide solution is also limited as follows: First, the volume percentage concentration of hydrogen peroxide solution is limited to 5%-30%. If it is lower than this range, the concentration is too low to gel, and if it is higher than this range, it will not only waste raw materials but also cause toxicity. Secondly, the amount of hydrogen peroxide solution used is limited to a volume ratio of 1:5-30 with the mixed solution: if it is lower than this range, the concentration is too low to gel, while if it is higher than this range, it will produce cytotoxicity; Therefore, the invention does not produce toxicity and has strong biocompatibility.
[0021] 4. In the method for preparing a bone nail based on light-cured silk fibroin of the present invention, whether it is the mixing of silk fibroin solution, riboflavin aqueous solution, hydrogen peroxide solution, or the spraying, ultraviolet light irradiation, mold opening, dehydration, and drying after obtaining the precursor solution, there are no parameters that are difficult to control, such as rotation speed and concentration, and there are no high-precision equipment requirements and difficult-to-reach or control temperature requirements. It is very easy to control, which not only makes the design easy to implement, but also facilitates popularization and application. Therefore, the present invention is not only easy to operate, but also has a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a physical picture of the bone screw prepared in Example 1 of the present invention in a dry state.
[0023] Figure 2 This is a physical picture of the bone screw prepared in Example 1 of the present invention in a wet state.
[0024] Figure 3 It is a schematic diagram characterizing the mechanical properties of the bone screw prepared in Example 1 of the present invention.
[0025] Figure 4 This is a confocal image of live staining of osteoblasts cultured on the surface of the bone screw prepared in Example 1 of the present invention on the third day.
[0026] Figure 5 This is a confocal image of dead cells stained on the surface of the bone screw prepared in Example 1 of the present invention after osteoblasts were cultured on the third day.
[0027] Figure 6 This is a confocal image of live / dead Merge staining of osteoblasts cultured on the surface of the bone screw prepared in Example 1 of the present invention on the third day. DETAILED DESCRIPTION
[0028] The present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0029] See also Figure 1 — Figure 6 , a method for preparing a bone nail based on light-cured silk fibroin, the preparation method comprising the following steps: The first step: firstly, the silk fibroin solution and the riboflavin aqueous solution are uniformly mixed to obtain a mixed solution, and then the hydrogen peroxide solution is added to the mixed solution to mix to obtain a precursor solution; The concentration of the silk fibroin solution is 8-15wt%, the concentration of the riboflavin aqueous solution is 0.05-10mmol / L, and the volume ratio between the silk fibroin solution and the riboflavin aqueous solution is 5-20:1; Step 2: first pour the precursor solution into a light-transmitting bone screw mold, and then place the bone screw mold under ultraviolet light for illumination to cause a photocuring reaction until the precursor solution is completely gelled; Step 3: First, place the bone screw mold in a freezing environment for demoulding, then place the removed bone screw blank in anhydrous ethanol for dehydration, and then dry it to obtain the bone screw.
[0030] In the second step, the parameters of the ultraviolet light irradiation are: the power of the ultraviolet lamp is 100-900W, and the light curing reaction time is 2-30min.
[0031] In the first step, the process for obtaining the post-silk fibroin solution is as follows: first obtain a pre-silk fibroin solution with a concentration of 1.5-7wt%, then put the pre-silk fibroin solution into a dialysis bag, and then place the dialysis bag into a polyethylene glycol solution with a mass percentage concentration of 10%-30% (preferably 20%) for concentration, until the concentration of the pre-silk fibroin solution is concentrated to 8-15wt%, thereby obtaining the post-silk fibroin solution.
[0032] The concentration time is 8-12 hours.
[0033] The process for obtaining the pre-silk fibroin solution is as follows: firstly, raw silk is placed in a sodium carbonate aqueous solution for heating and soaking to perform degumming treatment to obtain degummed silk fibroin fibers, then the degummed silk fibroin fibers are immersed in a LiBr aqueous solution for heating and dissolution to obtain a crude solution, then the crude solution is placed in a dialysis bag, and then the dialysis bag is placed in deionized water for low-temperature dialysis, the temperature of the low-temperature dialysis is 0-4°C, the time of the low-temperature dialysis is 1-5 days, then the remaining solution in the dialysis bag after dialysis is filtered to obtain a filtrate, and then the filtrate is diluted with deionized water to obtain a pre-silk fibroin solution, and the concentration of the pre-silk fibroin solution is 1.5-7wt%.
[0034] The concentration of the sodium carbonate aqueous solution is 0.1-0.5wt%, the mass volume ratio between the raw silk and the sodium carbonate aqueous solution is 1g / 10-100mL, the temperature of the degumming treatment is 45-100°C, and the time of the degumming treatment is 1-8h.
[0035] The concentration of the LiBr aqueous solution is 1-10 mol / L, the mass volume ratio between the degummed silk fiber and the LiBr aqueous solution is 1 g / 1-20 mL, the heating and dissolving temperature is 45-85° C., and the heating and dissolving time is 0.5-3 h.
[0036] In the first step, the volume percentage concentration of the hydrogen peroxide solution is 5%-30%, and the volume ratio between the hydrogen peroxide solution and the mixed solution is 1:5-30.
[0037] In the third step, the dehydration time of the anhydrous ethanol is 12-72 hours.
[0038] In the third step, the drying temperature is 40-80°C.
[0039] The supplementary technical features of the present invention are as follows: In the present invention, the freezing in a freezing environment for demoulding preferably refers to -20°C, and the specific operation is to disassemble the mold after freezing.
[0040] The polyethylene glycol in the present invention is referred to as PEG. The main reason why polyethylene glycol can concentrate the silk fibroin solution is that its hydrophilicity leads to the formation of hydrogen bonds with water molecules, the phase separation effect between the silk fibroin molecules, and the ability to induce conformational changes of the silk fibroin. These mechanisms work together to cause the silk fibroin to precipitate in the polyethylene glycol solution, thereby achieving the purpose of concentration.
[0041] The reason why the concentration time is limited to 8-12 hours in the present invention is that if the time is too short, the concentration will be insufficient and the concentration will be too low; if the time is too long, the concentration will be too high and gelation will occur, resulting in failure to use normally.
[0042] The reason why the volume ratio of the silk fibroin solution to the riboflavin aqueous solution is limited to 5-20:1 in the present invention is that if the silk fibroin solution is too little, gelation cannot occur, and if the silk fibroin solution is too much, it will be wasted.
[0043] The reason why the concentration of the silk fibroin solution is limited to 8-15wt% in the present invention is that the main purpose of concentration is to improve the mechanical properties. Since bone screws are made and hardness is sought, the concentration of the base material must be increased.
[0044] Embodiment 1: A method for preparing a bone nail based on light-cured silk fibroin, the method comprising the following steps: The first step: firstly, the post-silk fibroin solution and the riboflavin aqueous solution are uniformly mixed to obtain a mixed solution, and then the hydrogen peroxide solution is added to the mixed solution for mixing to obtain a precursor solution; the concentration of the post-silk fibroin solution is 8wt%, the concentration of the riboflavin aqueous solution is 0.5mmol / L, and the volume ratio between the silk fibroin solution and the riboflavin aqueous solution is 20:1; the volume percentage concentration of the hydrogen peroxide solution is 30%, and the volume ratio between the hydrogen peroxide solution and the mixed solution is 1:30; Step 2: first pour the precursor solution into a light-transmitting bone screw mold, and then place the bone screw mold under ultraviolet light for illumination to cause a photocuring reaction until the precursor solution is completely gelled; Step 3: First, place the bone screw mold in a freezing environment for demoulding, then place the removed bone screw blank in anhydrous ethanol for dehydration for 14 hours, and then place it in a 60°C oven for 24 hours to obtain the bone screw.
[0045] The wet state of the bone screw is in the form of a hydrogel, which contains a large amount of water. When it is immersed in ethanol, the water in the hydrogel is replaced by ethanol, causing the hydrogel to shrink and form a dense structure, which will cause the bone screw to shrink to a certain extent after drying, but the shape of the thread remains good and the deformation is not serious. In order to explore whether the bone screw will change its shape after drying, the inventor took photos of the prepared hydrogel bone screw (wet state) and the bone screw after drying for comparison.
[0046] Figure 1 This is a physical picture of the dry state of the silk fibroin bone nail prepared in Example 1. Figure 2 This is a real picture in wet state. By comparing with each other, it can be seen that the size of the bone screw after drying is reduced to 70% of the initial size, about 2mm, and the thread of the bone screw is uniform and clear.
[0047] The mechanical properties of bone screws are one of the key factors in determining whether they are suitable for bone repair. In order to investigate whether dried bone screws can be implanted into bones and whether the mechanical properties will decrease after implantation, we characterized the mechanical properties of the dried bone screws. Figure 3 As shown in the figure, the compressive strength of the dry bone screw reached a Young's modulus of about 160 MPa, which greatly exceeded the strength requirement of human cancellous bone and provided a theoretical basis for the implantation of the dry bone screw into human cancellous bone.
[0048] Finally, the inventors also tested the biocompatibility of the bone screw prepared in Example 1, cultured osteoblasts on the surface of the bone screw, and then cultured them in a 37°C carbon dioxide (5%) incubator, and photographed the growth state of the cells on the hydrogel surface using a confocal laser scanning microscopy (CLSM). Figures 4 to 6 This is a confocal image of live / dead staining of cells on the third day of cell culture, where: Figure 4 This is a confocal image of live staining of cells on the third day of culture (green fluorescent spots are living cells). Figure 5 This is a confocal image of dead cells on the third day of culture (the red fluorescent dots are dead cells). Figure 6 This is a confocal image of live / dead merge staining of cells on the third day of culture. Figures 4 to 6 It can be seen that the bone nail prepared in Example 1 has good cell survival status, has excellent biocompatibility with osteoblasts, and the material is non-toxic, and has great application potential in the field of bone repair.
[0049] Embodiment 2: The basic content is the same as that of Example 1, except that: The process for obtaining the post-silk fibroin solution is as follows: first, 30 g of raw silk is placed in 900 mL of a 0.1 wt% sodium carbonate aqueous solution, boiled and soaked for 1.5 h for degumming to obtain degummed silk fibroin fibers, and then the degummed silk fibroin fibers are immersed in 300 mL of a 10 mol / L LiBr aqueous solution, heated to 80° C. and dissolved for 3 h to obtain a crude solution, and then the crude solution is placed in a dialysis bag, and then dialyzed in 0° C. deionized water for 5 days, and then the dialyzed solution is filtered to remove impurities to obtain a pre-silk fibroin solution, and then the pre-silk fibroin solution is placed in a dialysis bag and placed in a 20% polyethylene glycol (PEG) solution for concentration for 10 h to obtain a post-silk fibroin solution with a mass fraction of 8 wt%.
[0050] The above description is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiment. Any equivalent modifications or changes made by ordinary technicians in this field based on the contents disclosed by the present invention should be included in the protection scope recorded in the claims.
Claims
1. A method for preparing a bone nail based on light-cured silk fibroin, characterized in that: The preparation method comprises the following steps: The first step: firstly, the silk fibroin solution and the riboflavin aqueous solution are uniformly mixed to obtain a mixed solution, and then the hydrogen peroxide solution is added to the mixed solution to mix to obtain a precursor solution; The concentration of the silk fibroin solution is 8-15wt%, the concentration of the riboflavin aqueous solution is 0.05-10mmol / L, and the volume ratio between the silk fibroin solution and the riboflavin aqueous solution is 5-20:1; Step 2: first pour the precursor solution into a light-transmitting bone screw mold, and then place the bone screw mold under ultraviolet light for illumination to cause a photocuring reaction until the precursor solution is completely gelled; Step 3: First, place the bone screw mold in a freezing environment for demoulding, then place the removed bone screw blank in anhydrous ethanol for dehydration, and then dry it to obtain the bone screw.
2. The method for preparing a bone nail based on light-cured silk fibroin according to claim 1, characterized in that: In the second step, the parameters of the ultraviolet light irradiation are: the power of the ultraviolet lamp is 100-900W, and the light curing reaction time is 2-30min.
3. A method for preparing a bone nail based on light-cured silk fibroin according to claim 1 or 2, characterized in that: In the first step, the process for obtaining the silk fibroin solution is as follows: First, a pre-silk fibroin solution with a concentration of 1.5-7wt% is obtained, and then the pre-silk fibroin solution is loaded into a dialysis bag, and then the dialysis bag is placed in a polyethylene glycol solution with a mass percentage concentration of 10%-30% for concentration, until the concentration of the pre-silk fibroin solution is concentrated to 8-15wt%, thereby obtaining a post-silk fibroin solution.
4. The method for preparing a bone nail based on light-cured silk fibroin according to claim 3, characterized in that: The concentration time is 8-12 hours.
5. The method for preparing a bone nail based on light-cured silk fibroin according to claim 3, characterized in that: The process for obtaining the pre-silk fibroin solution is as follows: First, the raw silk is placed in a sodium carbonate aqueous solution and heated and immersed for degumming to obtain degummed silk fibers, and then the degummed silk fibers are immersed in a LiBr aqueous solution and heated to dissolve to obtain a crude solution, and then the crude solution is placed in a dialysis bag, and then the dialysis bag is placed in deionized water for low-temperature dialysis, the temperature of the low-temperature dialysis is 0-4°C, the time of the low-temperature dialysis is 1-5 days, and then the remaining solution in the dialysis bag after dialysis is filtered to obtain a filtrate, and then the filtrate is diluted with deionized water to obtain a pre-silk fibroin solution, and the concentration of the pre-silk fibroin solution is 1.5-7wt%.
6. The method for preparing a bone nail based on light-cured silk fibroin according to claim 5, characterized in that: The concentration of the sodium carbonate aqueous solution is 0.1-0.5wt%, the mass volume ratio between the raw silk and the sodium carbonate aqueous solution is 1g / 10-100mL, the temperature of the degumming treatment is 45-100°C, and the time of the degumming treatment is 1-8h.
7. The method for preparing a bone nail based on light-cured silk fibroin according to claim 5, characterized in that: The concentration of the LiBr aqueous solution is 1-10 mol / L, the mass volume ratio between the degummed silk fiber and the LiBr aqueous solution is 1 g / 1-20 mL, the heating and dissolving temperature is 45-85° C., and the heating and dissolving time is 0.5-3 h.
8. The method for preparing a bone nail based on light-cured silk fibroin according to claim 1 or 2, characterized in that: In the first step, the volume percentage concentration of the hydrogen peroxide solution is 5%-30%, and the volume ratio between the hydrogen peroxide solution and the mixed solution is 1:5-30.
9. A method for preparing a bone nail based on light-cured silk fibroin according to claim 1 or 2, characterized in that: In the third step, the dehydration time of the anhydrous ethanol is 12-72 hours.
10. The method for preparing a bone nail based on light-cured silk fibroin according to claim 1 or 2, characterized in that: In the third step, the drying temperature is 40-80°C.